تكريس المشرع الجزائري لنظام وقف تنفيذ القرار الإداري المطعون فيه بالإلغاء - يونس, عطاب; محمد, بودواية (Université de M'sila, 2020)
ملخص : عندما يتم الطعن في القرار الإداري بالإلغاء أمام القضاء الإداري، فإن المبدأ العام يقضي تنفيذ القرار الإداري بالرغم من الطعن القضائي، لعدة اعتبارات قانونية وعملية، ضمانا لسير المرفق العام وعدم شل العمل الإداري اليومي، ولكن مع ذلك يمكن وقف تنفيذ هذا القرار في بعض الأحيان حفاظا على عدم ضياع حقوق الأفراد في حالة إلغاء القرار الإداري ولم يتم وقف تنفيذه أثناء الفصل في النزاع. وقد تبنى المشرع الجزائري نظام الوقف من خلال النص عليه في قانون الإجراءات المدنية والإدارية لسنة 2008، وفي قوانين أخرى كقانون نزع الملكية، وبالتالي وضع حد لامتياز الإدارة في تنفيذ قراراتها، إذ لا يمكن أن يكون هذا الامتياز على إطلاقه، لأن من شأنه إلحاق أضرار بالأفراد لا يمكن تداركها إذا كان القرار الإداري مشوب بعدم المشروعية وتم إلغاؤه، لذا كان لابد من وضع حد لهذا الامتياز للمحافظة على حقوق الأفراد من خلال إيقاف سريان أثره مؤقتا إلى حين الفصل فيه من طرف القضاء. Abstract: When the administrative decision is challenged before the administrative judiciary, the general principle is implement the administrative decision, despite the judicial challenged due to many legal and practical considerations, In order to ensure the functioning of the general Facility and not to disrupt the day-to-day administrative work, but the implementation of this resolution may sometimes be suspended In order to preserve the loss of the rights of individuals in the case of cancellation of the administrative decision and was not suspended during separation at the conflict. The Algerian legislator has adopted the stop execution system through the civil and Administrative Procedures law of 2008, and in other laws such as the expropriation law, and thus end the privilege of management in the implementation of its decisions, as this can not be a privilege to launch, Since it may cause harm to individuals and can not be remedied if the administrative decision is illegal and has been rescinded, It was therefore necessary to put an end to this privilege in order to preserve the rights of individuals by temporarily suspending the effect of the administrative decision until it was Separation in it before the judiciary.
Keywords: الكلمات المفتاحية: القرار الإداري- وقف التنفيذ- امتيازات الإدارة-حقوق الأفراد- دعوى الإلغاء. ; Key words: administrative decision - stop the implementation - privilege of administration- rights of individuals- cancellation Lawsuit